2007
DOI: 10.1016/j.jhsb.2007.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Cold Intolerance Following Median and Ulnar Nerve Injuries: Prognosis and Predictors

Abstract: This study describes the predictors for cold intolerance and the relationship to sensory recovery after median and ulnar nerve injuries. The study population consisted of 107 patients 2 to 10 years after median, ulnar or combined median and ulnar nerve injuries. Patients were asked to fill out the Cold Intolerance Severity Score (CISS) questionnaire and sensory recovery was measured using Semmes-Weinstein monofilaments. Fifty-six percent of the patients with a single nerve injury and 70% with a combined nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 31 publications
0
51
1
1
Order By: Relevance
“…Pain may also be associated with cold sensitivity 15,27,28,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Pain may also be associated with cold sensitivity 15,27,28,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] . The present study showed that patients with peripheral nerve injury had high levels of cold sensitivity and disability and that disability was predicted by pain and cold sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of cold sensitivity are often attributed to poor outcome following traumatic peripheral nerve injuries and have been reported more frequently in patients with digital amputations and replantations. 86,87,[89][90][91][92][93][94][95][96][97][98][99][100] Several studies have supported the continuation of cold-sensitivity symptoms in patients with hand injuries and nerve injuries and following replantation. 89,91,92,97,101,102 Campbell and Kay evaluated 176 patients following hand injuries, 73% of whom reported cold-related symptoms; most of these were related to pain.…”
Section: Considerations Of Cold Sensitivity and Contextual (Psychosocmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In a study on patients with a hand fracture, the prevalence of cold intolerance was found to be 38%. In addition, cold intolerance is commonly reported by patients who have had Raynaud's disease, 9 -12 upper extremity trauma, digital replantations, [13][14][15][16][17][18][19][20][21][22] hand and arm vibration syndrome, and a radial forearm flap.…”
mentioning
confidence: 99%